1997
DOI: 10.1136/gut.41.6.845
|View full text |Cite
|
Sign up to set email alerts
|

Drinking habits as cofactors of risk for alcohol induced liver damage

Abstract: Background-The Dionysos Study is a cohort study of the prevalence of chronic liver disease in the general population of two northern Italian communities. It included 6917 subjects, aged 12-65 (69% of the total population). Aims-The aim of this part of the study was to examine the relationship of daily alcohol intake, type of alcoholic beverage consumed, and drinking patterns to the presence of alcohol induced liver damage in an open population. Patients and methods-6534 subjects, free of virus related chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
388
2
15

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 577 publications
(431 citation statements)
references
References 26 publications
20
388
2
15
Order By: Relevance
“…A recent cohort study among patients with alcoholic fatty liver in the UK found that those who drank >40 g/day of alcohol were at risk of developing cirrhosis (Teli et al, 1995). A cross-sectional population-based study in Italy found no increased risk of alcoholic liver disease below 30 g/day (Bellentani et al, 1997).…”
Section: Dose-effect Relationship and Threshold Of Safe Intakementioning
confidence: 99%
“…A recent cohort study among patients with alcoholic fatty liver in the UK found that those who drank >40 g/day of alcohol were at risk of developing cirrhosis (Teli et al, 1995). A cross-sectional population-based study in Italy found no increased risk of alcoholic liver disease below 30 g/day (Bellentani et al, 1997).…”
Section: Dose-effect Relationship and Threshold Of Safe Intakementioning
confidence: 99%
“…8 The first phase of the Dionysos Study provided important and novel information on the prevalence of CLD in a representative sample of apparently healthy subjects from the general population and allowed determination of the threshold of alcohol intake for liver damage. [8][9][10][11] Ten years later (2001)(2002), all of the residents of the same towns were invited by letter to participate in the second phase of the Dionysos study, aimed to define the incidence and natural history of CLD.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of alcohol induced liver injury there is a longstanding belief that the severity of disease is dependent on the cumulative dose and duration of alcohol consumption, with decades of heavy drinking needed to induce pathology. However, studies show that only about 25% of heavy drinkers develop steatohepatitis with less than 10% developing alcoholic cirrhosis [2,3]. Based on this, it has been suggested that exposure to environmental toxicants like cigarette smoke or the presence of pre-existing conditions like type 2 diabetes, obesity, hypercholesterolemia, and/or hyperglycemia; conditions linked to the cardiometabolic syndrome, could worsen liver disease in the chronic alcohol consumer.…”
Section: Introductionmentioning
confidence: 99%